2021
DOI: 10.1002/eat.23469
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms following treatment for anorexia nervosa: A systematic literature review

Abstract: Objective Gastrointestinal (GI) disturbances are a frequent and burdensome experience for patients with anorexia nervosa (AN). How GI symptoms respond to current interventions is not well characterized, yet is critical to facilitate treatment success, and to inform the development of new treatments for AN. Therefore, the aim of this systematic review was to identify which treatments are effective in improving GI symptoms in patients with AN. Method A systematic search for studies of AN treatments measuring GI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
0
12
1
Order By: Relevance
“…A systematic review of thirteen studies aimed to identify the most effective treatment approaches for GI disorders and AN [ 163 ]. An improvement in at least one or more GI symptoms was reported in 11 of the 13 studies, with all studies including nutritional rehabilitation, and half also included concurrent psychological treatment [ 163 ].…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of thirteen studies aimed to identify the most effective treatment approaches for GI disorders and AN [ 163 ]. An improvement in at least one or more GI symptoms was reported in 11 of the 13 studies, with all studies including nutritional rehabilitation, and half also included concurrent psychological treatment [ 163 ].…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
“…A systematic review of thirteen studies aimed to identify the most effective treatment approaches for GI disorders and AN [ 163 ]. An improvement in at least one or more GI symptoms was reported in 11 of the 13 studies, with all studies including nutritional rehabilitation, and half also included concurrent psychological treatment [ 163 ]. Emerging evidence on ED comorbidity with chronic GI disorders suggested that EDs are often misdiagnosed in children and adolescents due to the crossover of symptoms.…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
“…GI symptoms in AN seem to mainly resolve with standard nutritional rehabilitation (West et al, 2021). However, increasing GI symptoms during the course of treatment and persistence of symptoms beyond nutritional recovery are also seen (Boyd et al, 2010;Chapelon et al, 2021;Mack et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While nutritional rehabilitation, a cornerstone in the AN recovery process, has been shown to improve most of the GI symptoms suffered (West et al, 2021;Riedlinger et al, 2020), the process of nutritional treatment may worsen symptoms for patients. Dysfunctions of digestive processes such as secretion of enzymes & absorption (Takimoto et al, 2014;Winter et al, 2001) may worsen gut symptoms during refeeding.…”
Section: Gi Symptoms and Anmentioning
confidence: 99%
“…Whereas for others, the experience of GID may present as a culmination of disordered eating behaviours and psychological distress [ 6 , 7 ]. However, it is well documented that whilst GID presentation may change or improve during inpatient care [ 8 , 9 ], for many people symptoms persist after treatment for AN [ 10 ]. Therefore, greater consideration is needed regarding how GID may be targeted in the treatment of AN to improve outcomes.…”
Section: Introductionmentioning
confidence: 99%